If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 3y + -8 + 4y = 0 Reorder the terms: 12 + -8 + 3y + 4y = 0 Combine like terms: 12 + -8 = 4 4 + 3y + 4y = 0 Combine like terms: 3y + 4y = 7y 4 + 7y = 0 Solving 4 + 7y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 7y = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 7y = 0 + -4 7y = 0 + -4 Combine like terms: 0 + -4 = -4 7y = -4 Divide each side by '7'. y = -0.5714285714 Simplifying y = -0.5714285714
| 0.5x+5.4=8.6 | | 0=x^2+0-67 | | -3(x-3)=21 | | 5p+24.2=28.65 | | x+1.4x=500 | | -x-9=13-3x | | 0.45x+0.6=0.6x | | 4lnx=3 | | (5x+3)=(4x-1) | | (6x)=42 | | -22+5x=-4x+32 | | 9x(-1)-7=x | | -7-5[2x-5(10+6x)]= | | -3-x=-2x+8 | | (-0.75x+6)-(2.5x-1.9)= | | 2(3x+2)=2x+1+x | | 100=v+23 | | 7-3x=-4+13 | | 29z+15z+11z+35z+46z+14z= | | (m-n-1)(m-n+1)= | | 25=5r | | x+x+2=758 | | 42=7t | | 17-x=5+6 | | 5b+4=6b-4 | | 3-6x=4x+0 | | 4(2x)=100 | | 42x-45=-72 | | 5x-1+9x=4x-7 | | (6+3x)=x-18 | | 6n+4=28-11 | | 4w^2+12w+9=1169 |